<span>first, you have to turn (5y-4)^2 into (5y-4)(5y-4).
From there, you would FOIL, or multilpy the 5y by the 5y, which is 25y^2, the multiply the 5y by the -4, which is -20y, then multiply the -4 by the 5y which is -20y, and then multiply the -4 by the -4, which is 16. It would then look like this: 25y^2 - 20y - 20y +16. Then you would add (or in this case, subtract) like terms. You would add -20y and -20y, which is -40y. The end expression would be 25y^2 - 20y +16. Hope this helps!
</span>
Answer:
n = -3
Step-by-step explanation:
-96 = 4(6n - 6)
-96 = 24n - 24
-72 = 24n
-3 = n
<span>v = 4/3*pi*r^3
derivating both sides with respect to t
dv/dt = 4*pi*r^2*dr/dt
when d = 1.7, r = 0.85, and dv/dt = 2:
2 = 4*pi*(0.85)^2*dr/dt
thus
dr/dt = 1/(2pi*(0.85)^2)
=1/(2*3.14*0.85^2)
=0.22</span><span />
Answer:
3b^7a^6c^9/64
Step-by-step explanation:
Its math just use a calculator or something